1995
DOI: 10.1093/jnci/87.11.827
|View full text |Cite
|
Sign up to set email alerts
|

Oral Contraceptives and Breast Cancer Risk Among Younger Women

Abstract: The relationship between oral contraceptives and breast cancer in young women appears to have a biologic basis rather than to be an artifact or the result of bias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
92
2
2

Year Published

1996
1996
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(105 citation statements)
references
References 0 publications
8
92
2
2
Order By: Relevance
“…Although the primary aim of the WISH study was to examine breast cancer risk in younger women in relation to patterns of oral contraceptive use, 22 it was not designed specifically to evaluate hypotheses about lobular breast cancer. Lobular cancers are a small proportion of all breast cancer cases diagnosed, and the mean age at diagnosis for lobular breast cancer is older than the mean age at diagnosis for ductal cancer, 36 and so it was expected that there would be a small number of lobular cases in the WISH population.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the primary aim of the WISH study was to examine breast cancer risk in younger women in relation to patterns of oral contraceptive use, 22 it was not designed specifically to evaluate hypotheses about lobular breast cancer. Lobular cancers are a small proportion of all breast cancer cases diagnosed, and the mean age at diagnosis for lobular breast cancer is older than the mean age at diagnosis for ductal cancer, 36 and so it was expected that there would be a small number of lobular cases in the WISH population.…”
Section: Discussionmentioning
confidence: 99%
“…22 Cases were recruited from metropolitan Atlanta, GA, Seattle-Puget Sound, WA, and a 5-county area in central New Jersey and were defined as any woman between 20 and 44 years of age who was diagnosed with incident in situ or invasive breast cancer between May 1, 1990 and December 31, 1992. Eligible cases were identified using rapid reporting systems established in each of the 3 geographic areas and checks were made against population-based cancer registries in these same areas.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have suggested an increased risk associated with recent or current use of oral contraceptives (Romieu et al, 1989; WHO Collaborative Study of Neoplasia and Steroid Contraceptives, 1990;Rookus and van Leeuwen, 1994;Brinton et al, 1995). This was recently confirmed by the comprehensive meta-analysis of the Collaborative Group on Hormonal Factors in Breast Cancer (1996).…”
Section: Discussionmentioning
confidence: 94%